The importance of local observation wells, reanalysis, and satellite data on gravity anomaly, climate, and land use to improve groundwater management in the Urucuia aquifer system - Camilo, Björn Krause; Andrade, Pedro Lage; Eleutério, Julian Cardoso; Rodrigues, André Ferreira (Journal of South American earth sciences, 2024)
The Urucuia Aquifer System (UAS) is an important water source for multiple users and the perennity of the San Francisco River. However, it has been subject to intensive land use transition (LUT), which provoked concerns due to continuous groundwater depletion. Therefore, understanding this depletion and potential drivers is essential for improved management towards water security. In this study, satellite data of the GRACE-project and in-situ data of the RIMAS-project were used to quantify the groundwater depletion between 2003 and 2021. Two important drivers were assessed for their impact on the UAS: (i) climate variability and (ii) LUT. The impact of climate variability was evaluated by using the vertical water balance (VWB; rainfall - evapotranspiration) on basis of validated rainfall and air temperature data from reanalysis (1979–2020). LUT was retrieved from the MAPBIOMAS database (1985–2022). The UAS was subdivided into quadrants of 0.75 × 0.75° (6700 km2) to assess the spatial variation of groundwater depletion and its drivers. Groundwater depletion was characterized by trend analysis and contrasted with the temporal behavior of VWB and LUT across the UAS. The results show a continuous decrease of the groundwater table in the study period (−22 mm/y) with a steeper decline between 2012 and 2018 (−52 mm/y). A direct cause-effect-relation can be observed with the negative trend of the VWB, pushed by decreasing rainfall and increasing air temperature over time. On the other hand, groundwater depletion correlates with LUT and is more accentuated where native vegetation is replaced by irrigated crops. Moreover, the GRACE dataset could be used for regional studies, but in-situ monitoring is recommended for local management as validation (R2 = 56%) indicates an underestimation of groundwater depletion by satellite data. In conclusion, extending the in-situ monitoring network, limiting LUT, and irrigation are crucial to long-term sustainability of the UAS. [Display omitted] •Groundwater level declined in the UAS from 2003 to 2021.•Land use transition and climatic variability interfere with groundwater storage.•Satellite and reanalysis data have the potential to monitor groundwater sustainability.•Observation wells are essential to improve local and regional groundwater management.